2001
DOI: 10.1046/j.1365-2044.2001.02268-2.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of methoxamine in the resuscitation of epinephrine-resistant electromechanical dissociation

Abstract: We describe three cases of electromechanical dissociation under anaesthesia that were unresponsive to doses of intravenous epinephrine given according to current Advanced Life Support guidelines, but which responded immediately to the intravenous administration of the pure alpha agonist, methoxamine. We suggest a possible mechanism to explain this finding and review the literature on vasopressor drugs used for cardiopulmonary resuscitation during electromechanical dissociation. An intravenous alpha agonist, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…[77][78][79] Other small case series described successful results with administration of alternative ␣-agonists such as norepinephrine, 80 methoxamine, 81,82 and metaraminol. [83][84][85] Alternative vasoactive drugs (vasopressin, norepinephrine, methoxamine, and metaraminol) may be considered in cardiac arrest secondary to anaphylaxis that does not respond to epinephrine (Class IIb, LOE C).…”
Section: Vasopressorsmentioning
confidence: 99%
“…[77][78][79] Other small case series described successful results with administration of alternative ␣-agonists such as norepinephrine, 80 methoxamine, 81,82 and metaraminol. [83][84][85] Alternative vasoactive drugs (vasopressin, norepinephrine, methoxamine, and metaraminol) may be considered in cardiac arrest secondary to anaphylaxis that does not respond to epinephrine (Class IIb, LOE C).…”
Section: Vasopressorsmentioning
confidence: 99%
“…53 Methoxamine, a relatively specific a 1 -receptor agonist, was also successfully used to re-establish spontaneous circulation in patients with cardiac arrest from anaphylactic shock. 54,55 These reports demonstrated successful use of a-agonist in epinephrine-resistant cardiovascular collapse; however, their role in pregnant patients has not yet been studied. Furthermore, etilefrine, a sympathomimetic with b 1 -and a-agonist properties, was used in a case of maternal anaphylaxis following administration of ampicillin for intrapartum chemoprophylaxis.…”
Section: Other Vasopressorsmentioning
confidence: 96%
“…479 A small case series of patients with anaphylactic shock with or without cardiac arrest suggested that patients who did not respond to standard therapy may benefit from vasopressin (LOE 4). 480,481 A few small case series (LOE 4) have described promising initial findings with ␣-agonists such as norepinephrine, 482 methoxamine, 483 terlipressin, 484 and metaraminol. [485][486][487] A few small case reports (LOE 4) of cardiac arrest suggest cardiopulmonary bypass 488,489 or mechanical support of circulation 490 may be helpful in the setting of anaphylaxis.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Several case reports (LOE 4) document the use of a variety of interventions for cardiac arrest caused by anaphylaxis: 6 case reports support high dose ␣-1 receptor agonists: metaraminol, 485,486 methoxamine, 483,487 and norepinephrine. 482 Other case reports document the use of terlipressin, 484 vasopression, 481 steroids and antihistamines, 491 and cardiopulmonary bypass.…”
Section: Consensus On Sciencementioning
confidence: 99%